Communication Manners are Reviewed Through Students' Perceptions About Islamic Religious Lessons at School - Nanik, Nanik (UIN Fatmawati Sukarno Bengkulu, 2023)
This article describes the manners of communication when viewed from students' perceptions in Islamic religious studies. This study used a quantitative approach and was tested by simple linear regression analysis. The research sample was n = 110 students from the city of Bengkulu. The results showed that there was a positive influence between the understanding of Islamic religious studies on how to communicate properly and politely to students with an R Square value of 0.385 or 38.5%, the effect on the way students communicate at school.